Technology to assess and support self-management in serious mental illness - Depp, Colin A. (Dialogues Clin Neurosci, 2016)
The functional impairment associated with serious mental illness (SMI) places an immense burden on individuals and society, and disability often persists even after efficacious treatment of psychopathologic symptoms. Traditional methods of measuring functioning have limitations, and numerous obstacles reduce the reach and impact of evidence-based interventions developed to improve functioning in SMI. This review describes the potential of technological innovations for overcoming the challenges involved in both functional assessment and intervention in people with SMI. Ecological momentary assessment (EMA), which involves the repeated sampling of naturalistic behaviors and experiences while individuals carry out their daily lives, has provided a new window through which the determinants of day-to-day function in SMI can be observed. EMA has several advantages over traditional assessment methods and has in recent years evolved to use mobile-based platforms, such as text messaging and smartphone applications, for both assessment and promotion of self-management in people with SMI. We will review promising data regarding the acceptability, adherence, and efficacy of EMA-based mobile technologies; explore ways in which these technologies can extend the reach and impact of evidence-based psychosocial rehabilitative interventions in SMI; and outline future directions for research in this important area.